Risk Pathways Contributing to the Alcohol Harm Paradox: Socioeconomic Deprivation Confers Susceptibility to Alcohol Dependence via Greater Exposure to Aversive Experience, Internalizing Symptoms and Drinking to Cope - Shuai, Ruichong; Anker, Justin J.; Bravo, Adrian J.; Kushner, Matt G.; Hogarth, Lee (Frontiers in Behavioral Neuroscience, 2022)
Socioeconomic deprivation is associated with greater alcohol problems despite lower alcohol consumption, but the mechanisms underpinning this alcohol harm paradox remain obscure. Fragmented published evidence collectively supports a multistage causal risk pathway wherein socioeconomic deprivation increases the probability of exposure to aversive experience, which promotes internalizing symptoms (depression and anxiety), which promotes drinking alcohol to cope with negative affect, which in turn accelerates the transition from alcohol use to dependence. To evaluate this proposed risk pathway, 219 hazardous drinkers from an undergraduate population completed questionnaires assessing these constructs in a single, cross sectional, online survey. Partial correlation coefficients revealed that each variable showed the strongest unique association with the next variable in the proposed multistage model, when adjusting for the other variables. Bootstrapped serial mediation analysis revealed that the indirect pathway linking all the variables in the proposed serial order was significant, while all other permutations were nonsignificant. Network centrality analysis corroborated the serial order of this indirect path. Finally, risk ratios estimated by categorising the variables suggested that socioeconomic deprivation increased the risk of aversive experience by 32%, which increased the risk of internalizing symptoms by 180%, which increased the risk of drinking to cope by 64%, which increased susceptibility to alcohol dependence by 59%. These preliminary findings need to be corroborated by future research, nevertheless, they call for prevention strategies founded on social justice and the minimization of aversive experience in socially deprived individuals to mitigate mental health problems, maladaptive coping and addiction.